2012
DOI: 10.1021/jf304398v
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Solubility and Stability Enhancement of Astilbin through Complexation with Cyclodextrins

Abstract: The complexation of astilbin with α-, β-, and γ-cyclodextrin (CD) was studied by phase solubility test and UV-vis spectral titration. Complexation with CDs gradually decreased the absorbance of astilbin at 291 nm and obviously increased its water solubility. The formation constant (K(a)) between astilbin and the three CDs was calculated. The stability of astilbin complexes increased in the order α-CD < γ-CD < β-CD, attributed to the CDs' cavity size. Temperature studies showed that the K(a) value decreased alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…Proposed mechanism for the biotransformation by supplementation of L-glutamine (200 mM) plus glycine (500 mM) in b-CD-water system It was reported that b-CD could enhance the solubility and bioavailability of hydrophobic substrates (Zidovetzki and Levitan, 2007). Moreover, b-CD can form a complex with such compounds (Zhang et al, 2013). As shown in Fig.…”
Section: Asymmetric Reduction Of Cobe By Supplementation Of L-glutamimentioning
confidence: 99%
See 2 more Smart Citations
“…Proposed mechanism for the biotransformation by supplementation of L-glutamine (200 mM) plus glycine (500 mM) in b-CD-water system It was reported that b-CD could enhance the solubility and bioavailability of hydrophobic substrates (Zidovetzki and Levitan, 2007). Moreover, b-CD can form a complex with such compounds (Zhang et al, 2013). As shown in Fig.…”
Section: Asymmetric Reduction Of Cobe By Supplementation Of L-glutamimentioning
confidence: 99%
“…S2A in the Supplementary materials available on-line, the diminished transmittances of the C@O group at 1731 and 1659 cm À1 by infrared spectrometry indicated that the substrate molecule COBE had been included by b-CD. Moreover, inclusion complex formation with b-CDs often causes UV-vis spectral changes of substrates (Zhang et al, 2013). With the addition of b-CD, the absorption maximum of COBE at 236 nm was red-shifted to 246 nm at pH 7.0, whereas the absorbance decreased gradually.…”
Section: Asymmetric Reduction Of Cobe By Supplementation Of L-glutamimentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous works showed that astilbin, the most dominant flavonoid in RSG , is a poorly soluble compound. However, β‐CD could significantly increase its solubility through complexes formation (Zhang, Cheung, & Zeng, ; Zhang, Nie et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been applied to increase the solubility and bioavailability of phytochemicals, nutraceuticals, and food additives through delivery systems such as microemulsions, 8−11 nanoemulsions, 12−14 solid lipid nanoparticles, 15 complexation with cyclodextrin, 16 and liposome encapsulation. 17 Among them, microemulsions (ME) have attracted much interest in recent years as drug delivery systems because they are not only highly dispersed, stable, and transparent systems and easily prepared but also help to improve the solubility and stability of many food and medical bioactive components.…”
Section: ■ Introductionmentioning
confidence: 99%